Growth and gas exchange in millet under different doses and sources of nitrogen (Research, Society and Development, 2020)
The objective was to evaluate growth, dry matter production (DMP) and gas exchange of millet, according to different doses and sources of nitrogen. The design was completely randomized in a 5 x 2 factorial scheme, with five nitrogen doses (40; 60; 80; 100 and 120 kg ha-¹ of N) and two sources of N (urea and ammonium sulfate). The evaluations were carried out at 60 and 85 days after seeding (DAS). The variables leaf area (AF), plant height (AP) and DMP at 60 and 85 DAS and stem diameter (SD at 85 DAS) were influenced by the interaction of N sources and doses. The SD at 60 DAS was influenced only doses. Stomatal conductance (gs) and chlorophyll content were influenced by the interaction between sources and doses, while the rate of CO2 assimilation (A) and transpiration (E) were influenced only by the dose. The nitrogen fertilization, in both sources, influenced the growth and the DMP of the millet, in the different periods of development (60 and 85 DAS). Urea showed a better response to gas exchange than ammonium sulfate, except for stomatal conductance. Thus, up to 60 days after seeding, for grazing purpose, between 60 and 80 kg ha-1 of N is recommended, using urea as the source. For the silage production, from 60 to 85 days after seeding, fertilization between 80 and 100 kg ha-1 of N in the form of urea is recommended.